2008
DOI: 10.4278/ajhp.22.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Hearts and Minds of Policy Makers: An Exploratory Study Associated with the West Virginia Walks Campaign

Abstract: Integrated communitywide health promotion campaigns designed to influence the public can also affect the perceptions of policy makers. Future research should examine this linkage and determine whether resource allocation and policy changes follow such interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Our findings are consistent with previous research that has examined the prioritization of traffic issues among local policy decision makers. 1415 For example, Dill and colleagues found that traffic congestion was an important motivation for adopting land use policies among local planning officials. 14 Furthermore, state and local policymakers assessed in Hawaii considered increased traffic an extremely important policy priority.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous research that has examined the prioritization of traffic issues among local policy decision makers. 1415 For example, Dill and colleagues found that traffic congestion was an important motivation for adopting land use policies among local planning officials. 14 Furthermore, state and local policymakers assessed in Hawaii considered increased traffic an extremely important policy priority.…”
Section: Discussionmentioning
confidence: 99%
“…8, 9 Understanding policymaker priorities and how to better target messages for this audience is critical for translating scientific findings into policy actions 10, 11 and identifying leverage points in the policy process. Previous studies have explored issues important to local policymakers that could impact obesity 12, 13 or active living 1416 but have not addressed ways for public health professionals to strategically engage with policymakers to implement active living initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…22 The use of pre-paid business reply envelopes rather than stamped envelopes may have affected our response rate. 38 It is impossible to determine if those who did respond to our survey systematically differed than those who did not as we did not ask for identifying information other than political party and appointment status.…”
Section: Manuscript In Press -Journal Of Public Health Management Andmentioning
confidence: 99%
“…22 A concurrent pilot study investigated the effects of the campaign on problem identification among policymakers.…”
mentioning
confidence: 99%